Bis(pentafluorophenyl)borane Induced Tandem Hydroboration-Carboboration of Cyclooctatetraene - Müller, Tizian; Hasenbeck, Max; Becker, Jonathan; Gellrich, Urs; Justus Liebig University Giessen (My University, 2023)
We report here the formation of the bridged boracycle 1 upon reaction of cyclooctatetraene with bis(pentafluorophenyl)borane. Computations indicate that the reaction commences with a hydroboration and that the high Lewis acidity of the bis(pentafluorophenyl)borane then induces a rearrangement with cleavage of a carbon–carbon bond via a nonclassical zwitterion and a final 1,1-carboboration. An intermediate of the reaction was captured as tri-tert-butylphosphine adduct.
Keywords: Hydroboration; Carboboration; Rearrangement; Density functional calculations; Lewis acid; ddc:540